Deep Learning-Based Early Prediction of Syncope Onset During Tilt Table Testing via Temporal Convolutional Autoencoder Anomaly Detector - Alex Wee Wong; Wee Jian Chin; Maw Pin Tan; Siew-Ying Mok; Choon-Hian Goh (Annals of Biomedical Engineering, 2026)

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Characterizing the marine recreational fishery of Hong Kong using data compiled from a social media platform - Bi Wei Low; Hilton H.C. Fu; Harris C.Y. Poon; Alex H.B. Liu; Heok Hui Tan; Kelvin K.P. Lim; Anthony Lau (Regional Studies in Marine Science, 2025)

The pluralistic natural capital values of a tropical city - Adrienne Grêt-Regamey; Justine Saunders; Peter Edwards; Daniel Richards; Jahson I. Alemu; Natasha Bhatia; Roman Carrasco; Zuzana Drillet; Tze Kwan Fung; Yan Feng Leon Gaw; Wanggi Jaung; Andrea Law; et al. (Ecosystem Services, 2025)

How much data do you need? An analysis of pelvic multi-organ segmentation in a limited data context - Febrio Lunardo; Laura Baker; Alex Tan; John Baines; Timothy Squire; Jason A. Dowling; Mostafa Rahimi Azghadi; Ashley G. Gillman (Physical and Engineering Sciences in Medicine, 2025)
Training deep learning models generally requires large, costly datasets which can limit their application towards in-house segmentation tasks. This study investigates the trade-off in dataset size within the context of pelvic multi-organ MR segmentation where we evaluate the performance of nnU-Net, a well-known segmentation model, under conditions of limited domain and data availability. 12 participants undergoing treatment on an Elekta Unity were recruited, acquiring 58 MR images, with 4 participants (12 images) withheld for testing. Prostate, seminal vesicles (SV), bladder and rectum were contoured in each image by a radiation oncologist. Seven models were trained on progressively smaller subsets of the training dataset, simulating a limited dataset setting. To investigate the efficacy of data augmentation, another set of identical models were trained without augmentation. The performance of the networks was evaluated via the Dice Similarity Coefficient, mean surface distance, and 95% Hausdorff distance metrics. When trained with entire training dataset (46 images), the model achieved a mean Dice coefficient of 0.903 (Prostate), 0.851 (SV), 0.884 (Rectum) and 0.967 (Bladder). Segmentation performance remained stable when the number of training sets was > 12 images from 4 participants, but rapidly dropped in smaller data subsets. Data augmentation was found to be influential across all dataset sizes, but especially in very small datasets. This study demonstrated nnU-Net's proficiency in performing male pelvic multi-organ segmentation under a limited domain, a single scanner, and under limited data constraints. We found that the performance degradation was often modest until a threshold is reached (12 images), below which it dropped significantly. Data augmentation improved performance across all data sizes, but especially for very small datasets. We conclude that nnU-Net’s low data requirement can be advantageous for in-house cases with consistent protocol and scarce data availability.

Uncertainties of biogenic VOC emissions caused by land cover data and implications on ozone mitigation strategies for the Yangtze river Delta region - Ling Huang; Xiaohui Zhao; Chuchu Chen; Jiani Tan; Yuewu Li; Hui Chen; Yangjun Wang; Li Li; Alex Guenther; Huan Huang (Atmospheric Environment, 2024)

Inverting continuous in-tunnel passive seismic data for velocity structure mapping ahead of the TBM cutterhead - Enhedelihai Alex Nilot; Yunyue Elita Li; Gang Fang; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2024)

Physicochemical characteristics of grease-trap wastewater with different potential mechanisms of FOG solid formation, separation, and accumulation inside grease traps - Ling Ying Tang; Ngie Hing Wong; Thion Am Chieng; Alex Kwong Jun Kiu; Chung Siung Choo; Yali Li; Chin Ping Tan; Abu Zahrim Yaser; Deni Shidqi Khaerudini; Gui Hua Chen; Jaka Sunarso (Water Research, 2024)

Quantifying tunneling risks ahead of TBM using Bayesian inference on continuous seismic data - Gang Fang; Enhedelihai Alex Nilot; Yunyue Elita Li; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2024)

An explicit review and proposal of an integrated framework system to mitigate the baffling complexities induced by road dust-associated contaminants - Yuxiao Zhang; Alex Justice Frimpong; Jingning Tang; Isaac Oyeyemi Olayode; Sampson Kofi Kyei; Prince Owusu-Ansah; Philip Kwabena Agyeman; Jamshid Valiev Fayzullayevich; Gangfeng Tan (Environmental Pollution, 2024)

The effects of plastic additives on swimming activity and startle response in marine amphipod Echinogammarus marinus - Bidemi Green-Ojo; Hung Tan; Marina Tenório Botelho; Henry Obanya; Lena Grinsted; Mathew O. Parker; Alex T. Ford (Science of The Total Environment, 2024)

Particle-bound reactive oxygen species in cooking emissions: Aging effects and cytotoxicity - Lu Lu; Vanessa Y.Z. Ng; Melvyn Z.H. Tan; Nethmi Y. Kasthuriarachchi; Laura-Helena Rivellini; Yue Qian Tan; Lina Ang; Maximillian Viera; Boon Huat Bay; Wei Jie Seow; Alex K.Y. Lee (Atmospheric Environment, 2024)

Experimental investigation supported by artificial neural networks (ANNs) for predicting the heating performance of a cyclone separator coupled with induction heating coil - Alex J. Frimpong; Gangfeng Tan; Yuxiao Zhang; Jiedong Ye; Philip K. Agyeman; Sampson K. Kyei; Isaac O. Olayode (Process Safety and Environmental Protection, 2023)

Exposure to cooking fumes is associated with perturbations in nasal microbiota composition: A pilot study - Xin Er Frances Jin; Dorrain Yanwen Low; Lina Ang; Lu Lu; Xin Yin; Yue Qian Tan; Alex King Yin Lee; Wei Jie Seow (Environmental Research, 2023)

Real-time tunneling risk forecasting using vibrations from the working TBM - Enhedelihai Alex Nilot; Gang Fang; Yunyue Elita Li; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Alterations of sarcoplasmic reticulum-mediated Ca2+ uptake in a model of premature ventricular contraction (PVC)-induced cardiomyopathy - Jaime Balderas-Villalobos; J. M. L. Medina-Contreras; Christopher Lynch; Rajiv Kabadi; Rafael J. Ramirez; Alex Y. Tan; Karoly Kaszala; Montserrat Samsó; Jose F. Huizar; Jose M. Eltit (Molecular and Cellular Biochemistry, 2023)

Transmission of viruses and other pathogenic microorganisms via road dust: Emissions, characterization, health risks, and mitigation measures - Frimpong J. Alex; Gangfeng Tan; Sampson K. Kyei; Prince O. Ansah; Philip K. Agyeman; Jamshid V. Fayzullayevich; Isaac O. Olayode (Atmospheric Pollution Research, 2023)

Investigating longitudinal changes to frontal cortico-striatal tracts in Huntington’s disease: the IMAGE-HD study - Brendan Tan; Rosita Shishegar; Stuart Oldham; Alex Fornito; Govinda Poudel; Nellie Georgiou-Karistianis (Brain Imaging and Behavior, 2022)
The striatum is the principal site of disease pathology in Huntington’s disease and contains neural connections to numerous cortical brain regions. Studies examining abnormalities to neural connections find that white matter integrity is compromised in HD; however, further regional, and longitudinal investigation is required. This paper is the first longitudinal investigation into region-based white-matter integrity changes in Huntington’s Disease. The aim of this study was to better understand how disease progression impacts white matter tracts connecting the striatum to the prefrontal and motor cortical regions in HD. We used existing neuroimaging data from IMAGE-HD, comprised of 25 pre-symptomatic, 27 symptomatic, and 25 healthy controls at three separate time points (baseline, 18-months, 30-months). Fractional anisotropy, axial diffusivity and radial diffusivity were derived as measures of white matter microstructure. The anatomical regions of interest were identified using the Desikan-Killiany brain atlas. A Group by Time repeated measures ANCOVA was conducted for each tract of interest and for each measure. We found significantly lower fractional anisotropy and significantly higher radial diffusivity in the symptomatic group, compared to both the pre-symptomatic group and controls (the latter two groups did not differ from each other), in the rostral middle frontal and superior frontal tracts; as well as significantly higher axial diffusivity in the rostral middle tracts only. We did not find a Group by Time interaction for any of the white matter integrity measures. These findings demonstrate that whilst the microstructure of white matter tracts, extending from the striatum to these regions of interest, are compromised during the symptomatic stages of Huntington’s disease, 36-month follow-up did not show progressive changes in these measures. Additionally, no correlations were found between clinical measures and tractography changes, indicating further investigations into the relationship between tractography changes and clinical symptoms in Huntington’s disease are required.

Longitudinal mapping of cortical surface changes in Huntington’s Disease - Brendan Tan; Rosita Shishegar; Alex Fornito; Govinda Poudel; Nellie Georgiou-Karistianis (Brain Imaging and Behavior, 2022)

Correction to: Shallowness of tropical low clouds as a predictor of climate models’ response to warming - Florent Brient; Tapio Schneider; Zhihong Tan; Sandrine Bony; Xin Qu; Alex Hall (Climate Dynamics, 2021)

Sphingomonas palmae sp. nov. and Sphingomonas gellani sp. nov., endophytically associated phyllosphere bacteria isolated from economically important crop plants - Munusamy Madhaiyan; Venkatakrishnan Sivaraj Saravanan; Joseph S. Wirth; Tan Hian Hwee Alex; Soo-Jin Kim; Hang-Yeon Weon; Soon-Wo Kwon; William B. Whitman; Lianghui Ji (Antonie van Leeuwenhoek, 2020)

Local and regional scale habitat heterogeneity contribute to genetic adaptation in a commercially important marine mollusc ( Haliotis rubra ) from southeastern Australia - Adam D. Miller; Ary A. Hoffmann; Mun Hua Tan; Mary Young; Collin Ahrens; Michael Cocomazzo; Alex Rattray; Daniel A. Ierodiaconou; Eric Treml; Craig D. H. Sherman (Molecular Ecology, 2019)
Characterising adaptive genetic divergence among conspecific populations is often achieved by studying genetic variation across defined environmental gradients. In marine systems this is challenging due to a paucity of information on habitat heterogeneity at local and regional scales and a dependency on sampling regimes that are typically limited to broad longitudinal and latitudinal environmental gradients. As a result, the spatial scales at which selection processes operate and the environmental factors that contribute to genetic adaptation in marine systems are likely to be unclear. In this study we explore patterns of adaptive genetic structuring in a commercially‐ harvested abalone species ( Haliotis rubra ) from southeastern Australia, using a panel of genome‐wide SNP markers (5,239 SNPs), and a sampling regime informed by marine LiDAR bathymetric imagery and 20‐year hindcasted oceanographic models. Despite a lack of overall genetic structure across the sampling distribution, significant genotype associations with heterogeneous habitat features were observed at local and regional spatial scales, including associations with wave energy, ocean current, sea surface temperature, and geology. These findings provide insights into the potential resilience of the species to changing marine climates and the role of migration and selection on recruitment processes, with implications for conservation and fisheries management. This study points to the spatial scales at which selection processes operate in marine systems and highlights the benefits of geospatially‐informed sampling regimes for overcoming limitations associated with marine population genomic research.

Reconstructing the invasion history of a spreading, non-native, tropical tree through a snapshot of current distribution, sizes, and growth rates - Kwek Yan Chong; Mark B. Raphael; L. Roman Carrasco; Alex T. K. Yee; Xingli Giam; Von Bing Yap; Hugh T. W. Tan (Plant Ecology, 2017)

Shallowness of tropical low clouds as a predictor of climate models’ response to warming - Florent Brient; Tapio Schneider; Zhihong Tan; Sandrine Bony; Xin Qu; Alex Hall (Climate Dynamics, 2016)

Diagnosis of East African climate and the circulation mechanisms associated with extreme wet and dry events: a study based on RegCM4 - Bob Alex Ogwang; Haishan Chen; Guirong Tan; Victor Ongoma; Didier Ntwali (Arabian Journal of Geosciences, 2015)

ANGPTL4 is produced by entero-endocrine cells in the human intestinal tract - Sheril Alex; Laeticia Lichtenstein; Wieneke Dijk; Ronald P. Mensink; Nguan Soon Tan; Sander Kersten (Histochemistry and Cell Biology, 2014)

Leaf litter depth as an important factor inhibiting seedling establishment of an exotic palm in tropical secondary forest patches - Hazelina H. T. Yeo; Kwek Yan Chong; Alex T. K. Yee; Xingli Giam; Richard T. Corlett; Hugh T. W. Tan (Biological Invasions, 2014)

Novel quantitative trait loci for central corneal thickness identified by candidate gene analysis of osteogenesis imperfecta genes - David P. Dimasi; Jern Y. Chen; Alex W. Hewitt; Sonja Klebe; Richard Davey; John Stirling; Elizabeth Thompson; Robin Forbes; Tiong Y. Tan; Ravi Savarirayan; David A. Mackey; Paul R. Healey; et al. (Human Genetics, 2010)

Human Multidrug Resistance Associated Protein 4 Confers Resistance to Camptothecins - Quan Tian; Jing Zhang; Theresa May Chin Tan; Eli Chan; Wei Duan; Sui Yung Chan; Urs Alex Boelsterli; Paul Chi-Lui Ho; Hongyuan Yang; Jin-Song Bian; Min Huang; Yi-Zhun Zhu; et al. (Pharmaceutical Research, 2005)